Potential Value of the Insights and Lived Experiences of Addiction Researchers With Addiction. Issue 2 (10th March 2022) - Stull, Samuel W.; Smith, Kirsten E.; Vest, Noel A.; Effinger, Devin P.; Epstein, David H.
Abstract : People in remission from substance use disorders (SUDs) have a history of using their own experience (also referred to as "experiential knowledge" or "expertise") to support those in or seeking SUD remission. In recent years, people with this experiential knowledge are being incorporated into research protocols to better guide research questions and inform the real-world uptake of SUD treatments and recovery supports. In these research contexts, however, those with research expertise and addiction rarely speak freely about these overlapping perspectives. The aim of this commentary is to increase awareness regarding the existence of this group (addiction researchers with addiction) and to explore the possibility that their expertise may help advance addiction science while helping to reduce stigma.